2011
DOI: 10.1002/ddr.20445
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate‐derived Fulvic acid (CHD‐FA) inhibits Carrageenan‐induced inflammation and enhances wound healing: efficacy and Toxicity study in rats

Abstract: The objectives of this study were to evaluate the safety and anti-inflammatory and wound healing characteristics of carbohydrate derived fulvic acid (CHD-FA) in rats.A daily oral dosage of CHD-FA at 100mg/kg and higher effectively reduced carrageenan-induced paw oedema in rats which was comparable to an oral dosage of 10mg/kg indomethacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 13 publications
3
27
0
2
Order By: Relevance
“…It has been reported that CHD-FA has no toxicity in rats and humans, and it has been further suggested that it elicits anti-inflammatory and wound healing promoting properties [17,28]. Periodontitis is characterised by chronic inflammation that leads to tissue and bone destruction [29], therefore controlling these processes is an attractive option for clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CHD-FA has no toxicity in rats and humans, and it has been further suggested that it elicits anti-inflammatory and wound healing promoting properties [17,28]. Periodontitis is characterised by chronic inflammation that leads to tissue and bone destruction [29], therefore controlling these processes is an attractive option for clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been recently reported to be non-toxic in a rat wound model, in addition to having anti-inflammatory properties (Sabi et al, 2011). A recent randomized, double blind, controlled trial indicated that fulvic acid was well-tolerated in a study of eczema (Gandy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The data suggested that the product was nontoxic with regards to liver and kidney function in rats over a period of 6 months, when administered orally. 6 …”
Section: Introductionmentioning
confidence: 99%